Supply Chain Risk Management via Enhanced Observability - Mekhaimer, Anis (Journal of Global Economy, Business and Finance, 2024)
Supply Chain Risk Management is crucial for maintaining the resilience and reliability of supply chains in today's complex and rapidly changing business environment. This paper explores the role of improved observability in enhancing SCRM efforts. Improved observability, which involves the visibility and understanding of real - time supply chain activities, has emerged as a key driver for effective risk management. By leveraging advanced technologies such as the Internet of Things, big data analytics, and blockchain, supply chain practitioners can gain granular insights into operations, thereby significantly improving their capability to identify, assess, and prioritize risks.